The Emergence of the American Mathematical Research Community, 1876-1900 : J.J. Sylvester, Felix Klein, and E.H. Moore. - Parshall, Karen Hunger (History of mathematics., 1994)
This volume traces the transformation of the United States from a mathematical backwater to a major presence during the quarter-century from 1876 to 1900. Presenting a detailed study of the major figures involved in this transformation, it focuses on the three most influential individuals-the British algebraist James Joseph Sylvester, the German standard-bearer Felix Klein, and the American mathematician Eliakim Hastings Moore-and on the principal institutions with which they were associated-the Johns Hopkins University, Göttingen University, and the University of Chicago. This book further an.